Isolation, Characterization, Antioxidant Activity, Metal-Chelating Activity, and Protein-Precipitating Capacity of Condensed Tannins from Plum (Prunus salicina) Fruit - Liangliang Zhang; He Zhang; Lihua Tang; Xinyu Hu; Man Xu (MDPI AG, 2022)
The type of polymeric condensed tannins from plum fruit (Prunus salicina) (PCT), the degree of polymerization and the distribution of polymers were characterized by MALDI-TOF MS and NMR spectroscopy. The metal-binding capacity of PCT with five metal ions (Cu2+, Zn2+, Al3+, Fe2+, and Fe3+) was characterized by a fluorescence quenching method. The results demonstrated the following: epicatechin was the basic unit occurring in PCT, and A-type and B-type linkages were the most common between the structural units of the polymers. The PCT have a strong antioxidant activity, which is comparable with that of the synthetic antioxidant BHA. The quenching mechanism of the PCT's fluorescence intensity by Zn2+, Cu2+, and Al3+ was different from that of Fe3+ and Fe2+. Fe3+, Al3+ and Fe2+ had much higher affinities for the PCT than Zn2+ and Cu2+. A simple UV-Vis spectra method was developed to determine the protein-precipitating capacity of tannins. Bovine serum albumin (BSA) was effectively precipitated by tannins isolated from plum fruits, Chinese gallnut, sorghum grain, and Platycarya strobilacea at pH values between 4.5 and 5.0. A statistically significant linear relationship (p < 0.0001 or p < 0.0003) existed between the amount of tannin-protein complex formed and the amount of tannins added to the reaction mixture. The slopes of these lines indicated the protein-precipitating capacity of tannins.